Modeling the Role of Elements on Positive Word-of-Mouth in the e-Banking - Mohammad Mousakhani; Samaneh Torkzadeh (Journal of Information Technology Management)
Positive word-of-mouth (P-WOM) has a strong influence on purchase decision of new customer. Today, firms try creating loyal customer with positive WOM and use from this competitive factor in increasing their market share. This research showed that website usability (WU) has a positive effect on customer satisfaction (CS), and also this element have a positive effect on customer loyalty (CL). CS and CL have a direct positive effect on word-of mouth; also WU has an indirect positive effect on P-WOM. Present research is applicable in purpose, and research method is analytical description with corresponding examine. After collecting data through questionnaire, hypotheses are contrasted with structural equation modeling (SEM) with Lisrel software. The study population included all branches customers of Bank Melli Iran of north Tehran.